A case of extensive burn without sepsis showing high level of plasma presepsin (sCD14-ST). Issue 1 (July 2017) - Hayashi, Masahiro; Yaguchi, Yoriko; Okamura, Ken; Goto, Emiko; Onodera, Yu; Sugiura, Asumi; Suzuki, Hiroto; Nakane, Masaki; Kawamae, Kaneyuki; Suzuki, Tamio
Highlights: Presepsin is a biomarker to detect the existence and severity of sepsis. Our patient had extensive burns without sepsis and a high presepsin level. His presepsin level decreased in parallel with his C-reactive protein level and wound closure. Presepsin level of this patient may be elevated with increased phagocytotic activity. We need to be aware some patients without sepsis may show high presepsin levels. Abstract: Presepsin (soluble CD14 subtype; sCD14-ST) is a biomarker that detects the existence and severity of sepsis. Previous studies have demonstrated that plasma presepsin levels can consistently distinguish systemic inflammatory response syndrome due to non-sepsis conditions from sepsis. We present a case report of a patient with extensive burns who showed high presepsin levels without sepsis. The 33-year-old man was transferred to the emergency room owing to burns on 33% of his total body surface area and inhalation injuries. He was intubated immediately and admitted to the intensive care unit. The patient's plasma presepsin level increased to 1984 ρg/mL on day 6. However, repeated blood, wound, and urine cultures did not isolate any pathogenic bacteria. Chest radiographs and enhanced computed tomography did not detect any infectious foci. The patient's Sequential Organ Failure Assessment score also did not meet the criteria for sepsis. After the patient's condition stabilized and he was extubated, his presepsin level decreased to 354 ρg/mL on day 13. Debridement and split-thickness mesh skin grafting were performed on day 14. The acceptance of the skin graft was excellent and the patient's condition improved after the surgery; he was discharged on day 59. Although presepsin has been reported to be a reliable biomarker, certain pathophysiological conditions may affect its levels, as indicated by this case. The reason for our patient's high presepsin level is unclear; however, the case serves as a reminder that presepsin levels may increase in patients without sepsis.